Numerical Study of the Aeroelastic Stability of an Overexpanded Rocket Nozzle - Lefran~ois, Emmanuel; Dhatt, Gouri; Vandromme, Dany (European Journal of Computational Mechanics, 2000)
A numerical model for studying aeroelastic stability is proposed in this paper with application to the overexpanded rocket engines. Starting from previous results obtained by Pekkari's team [PEK 93], the model is extended to take into account dynamic instabilities. A monodimensional model is used to check the effects of the chosen solicitation form on the global stability of a flexible nozzle. We observe that stability is influenced with the initial position of the separation shock. A static instability will be revealed by the presence of a zero value for one modal frequency, whereas a dynamic instability will appear after coalescing modes (similar to well-known flutter phenomena). Finally, a calculation is conducted in coupling two codes, one dedicated to structure dynamics, the second to the fluid phase in order to validate the stability model in the general two-dimensional case of an overexpanded rocket engine.